2009
DOI: 10.4049/jimmunol.0902447
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Basophils Are Transiently Recruited into the Draining Lymph Nodes during Helminth Infection via IL-3, but Infection-Induced Th2 Immunity Can Develop without Basophil Lymph Node Recruitment or IL-3

Abstract: Basophils are recognized as immune modulators through their ability to produce IL-4, a key cytokine required for Th2 immunity. It has also recently been reported that basophils are transiently recruited into the draining lymph node (LN) after allergen immunization and that the recruited basophils promote the differentiation of naive CD4 T cells into Th2 effector cells. Using IL-3−/− and IL-3Rβ−/− mice, we report in this study that the IL-3/IL-3R system is absolutely required to recruit circulating basophils in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
128
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(140 citation statements)
references
References 30 publications
10
128
0
1
Order By: Relevance
“…Interestingly, some studies suggest that ILC, 129-131 basophils, [132][133][134] and eosinophils 135,136 can express major histocompatibility complex class II and directly prime Th2 responses, notably upon N. brasiliensis 131 and T. muris 132 infections, with each cell type having been shown to migrate to the mesenteric lymph nodes during infection. 85,87,137,138 However, given that protective immunity is abolished in mice where all 139,140 or specific subsets 104-106,108,109 of dendritic cells have been depleted, it is perhaps more likely that these other innate cells contribute to local tissue immunity by promoting dendritic cell activation, or by further enhancing the cytokine response of mature T cells that have migrated to the infected tissue. 53 Moreover, dendritic cells are responsive not only to cytokines produced by other innate cells, but also to epithelium-derived cytokines, including TSLP, 54,[141][142][143] IL-25, 144 and IL-33, 52,145 thus potentially bypassing ILC2 and granulocytes entirely.…”
Section: Inductionmentioning
confidence: 99%
“…Interestingly, some studies suggest that ILC, 129-131 basophils, [132][133][134] and eosinophils 135,136 can express major histocompatibility complex class II and directly prime Th2 responses, notably upon N. brasiliensis 131 and T. muris 132 infections, with each cell type having been shown to migrate to the mesenteric lymph nodes during infection. 85,87,137,138 However, given that protective immunity is abolished in mice where all 139,140 or specific subsets 104-106,108,109 of dendritic cells have been depleted, it is perhaps more likely that these other innate cells contribute to local tissue immunity by promoting dendritic cell activation, or by further enhancing the cytokine response of mature T cells that have migrated to the infected tissue. 53 Moreover, dendritic cells are responsive not only to cytokines produced by other innate cells, but also to epithelium-derived cytokines, including TSLP, 54,[141][142][143] IL-25, 144 and IL-33, 52,145 thus potentially bypassing ILC2 and granulocytes entirely.…”
Section: Inductionmentioning
confidence: 99%
“…Basophils were proposed to function as APCs in these studies and were also shown to be present in LNs in models of allergy and helminth infection [12][13][14]. However, the function of basophils as APCs during the priming phase of Th2 responses in mice has been challenged by others [13,15,16], and human basophils could not present antigens to CD4 + T cells [17,18]. Therefore, it seems unlikely that human basophils function as APCs.…”
mentioning
confidence: 99%
“…Interestingly, IL-3 plays a key role in recruiting circulating basophils into the draining LN after Nb infection. 16 Similar to the papaininduced basophil recruitment, circulating basophils enter the draining mediastinal LN between days 3 and 4 post infection and the mesenteric LN around day 10 post infection, the kinetics of which closely matches the migration pattern of the parasites in vivo; thus the recruitment seems driven by antigen-mediated T-cell activation. Such recruitment is completely abolished in Nb infected mice deficient in IL-3 or IL-3 receptor.…”
Section: Basophils Induce Th2 Immunitymentioning
confidence: 71%
“…Such recruitment is completely abolished in Nb infected mice deficient in IL-3 or IL-3 receptor. 16 In vitro, IL-3 has been shown to upregulate expression of surface adhesion molecules and of chemokines in endothelial cells, both of which contribute to basophil adhesion as well as transendothelial migration. 17 In vivo, however, the target cells of IL-3 that mediates basophil LN entry were of bone marrow origin, arguing against the in vitro observation.…”
Section: Basophils Induce Th2 Immunitymentioning
confidence: 99%